2020
DOI: 10.1101/2020.05.20.106401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep immune profiling of COVID-19 patients reveals patient heterogeneity and distinct immunotypes with implications for therapeutic interventions

Abstract: COVID-19 has become a global pandemic. Immune dysregulation has been implicated, but immune responses remain poorly understood. We analyzed 71 COVID-19 patients compared to recovered and healthy subjects using high dimensional cytometry. Integrated analysis of ~200 immune and >30 clinical features revealed activation of T cell and B cell subsets, but only in some patients. A subgroup of patients had T cell activation characteristic of acute viral infection and plasmablast responses could reach >30% of circulat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
170
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(216 citation statements)
references
References 62 publications
39
170
1
6
Order By: Relevance
“…Compositional changes were not as readily apparent in PBMCs, although we observed an expansion of multiple plasma cell types in severe donors compared to healthy control subjects, consistent with previous reports [23,33,34,44].…”
Section: Indicated Expansion Of Nk Cells T Cells (General T Cell Popsupporting
confidence: 91%
“…Compositional changes were not as readily apparent in PBMCs, although we observed an expansion of multiple plasma cell types in severe donors compared to healthy control subjects, consistent with previous reports [23,33,34,44].…”
Section: Indicated Expansion Of Nk Cells T Cells (General T Cell Popsupporting
confidence: 91%
“…We also quantified the genes, surface proteins, and pathway enrichment scores in CD4 + T cells and their correlation with disease severity. Consistent with recent literature (Chen et al, 2020;Mathew et al, 2020), an increase of FAS pathway genes, proliferation genes, activation/effector surface markers CX3CR1, B7-H4, the Th1 differentiation pathway score, and the Type I interferon response gene signature were positively correlated with disease severity ( Figure 3I). By contrast, naïve T cell signatures and the earlyactivation marker CD27 were negatively correlated ( Figure 3I).…”
Section: Cd4 + T Cell Proliferation Cytotoxic Activity and Clonal Esupporting
confidence: 90%
“…Recorded signatures of immune dysregulation include lymphopenia that is commonly associated with reduced numbers of T cells, natural killer cells, and other lymphocytes (Cao, 2020;Ruan et al, 2020;Tan et al, 2020), as well as elevated exhaustion markers on immune cells (Zheng et al, 2020). Elevated levels of circulating inflammatory cytokines (Mathew et al, 2020) have been reported, although the primary source of such cytokines, as well as the roles of circulating T cells and monocytes, has been debated (Wilk et al, 2020;Zhou et al, 2020). A condition bearing similarities to IL-6-mediated cytokine release syndrome (CRS) (Yang et al, 2020) has also been reported in severely ill COVID-19 patients, although unlike in CRS in cancer patients receiving CAR-T immunotherapies, associated toxicity are less severe, and benefit of IL-6 blockade was less consistent (Vardhana and Wolchok, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…T cells are crucial for viral clearance and development of immunologic memory (Wherry and Ahmed, 2004) and are plausible contributors to immunopathology following viral infection (Channappanavar and Perlman, 2017). Both SARS-CoV-2 reactive CD4 and CD8 T cells have been detected in patients with COVID-19 (Chour et al, 2020;Grifoni et al, 2020a;Weiskopf et al, 2020a), though early studies suggest the relationship between T cell responses and the severity of COVID-19 is complex (Mathew et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, genetic susceptibilities to viral infection have been tied to variation in the major histocompatibility complex (MHC) genes that encode HLA proteins (Dutta et al, 2018;Hill, 2001). Meanwhile, functional differences in viral antigen-specific T cell responses in symptomatic and asymptomatic patients may also contribute to the biology of at-risk populations (Mathew et al, 2020;Weiskopf et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%